South Levantine harbor cities in the Herodian period – Early Roman imported fine and utilitarian wares from Ashdod and Ashkelon - Wołodźko, Paulina (Instytut Historyczny Uniwersytetu Wrocławskiego, 2020)
The article presents Ashdod and Ashkelon, two harbor cities from the Herodian period (37 BCE – 70 CE), located on the south Levantine’s coast. The topic is depicted using the examples of the imported fine and utilitarian wares dated to Early Roman, in specific Herodian, period. Ashdod and Ashkelon were cities located nearby, with very similar history up to the Hellenistic period. After this time their similarities disappeared and the importance in the region changed. This issue is well presented in the pottery assemblage and imports from the whole Mediterranean world.